Head Loss Characteristics in a Burnt Oil Palm Shell Granules Filter Compared to a Sand Filter and its Application in Rapid Filtration - Jusoh, Ahmad; Ghazali, Abdul Halim; Megat Mohd Noor, Megat Johari (Universiti Putra Malaysia Press, 1998)
Studies were carried out on the initial head loss and the operational head loss occurring in single medium filters of sand and burnt oil palm shell (BOPS) as well as in a dual-media filter consisting of these two materials. The experimental initial head loss values in filters were shown to agree with the values predicted by the well-known Fair and Hatch formula. The characteristics of the experimental operational head loss were quite similar to the Ives's prediction. The dual-media filter proved to be a cost effective technique for water filtration due to its long running time and high quality filtered water.